Neurometabolic coupling between neural activity, glucose, and lactate in activated visual cortex. (29th May 2015) - Li, Baowang; Freeman, Ralph D.
Abstract: Neural activity is closely coupled with energy metabolism but details of the association remain to be identified. One basic area involves the relationships between neural activity and the main supportive substrates of glucose and lactate. This is of fundamental significance for the interpretation of non‐invasive neural imaging. Here, we use microelectrodes with high spatial and temporal resolution to determine simultaneous co‐localized changes in glucose, lactate, and neural activity during visual activation of the cerebral cortex in the cat. Tissue glucose and lactate concentration levels are measured with electrochemical microelectrodes while neural spiking activity and local field potentials are sampled by a microelectrode. These measurements are performed simultaneously while neurons are activated by visual stimuli of different contrast levels, orientations, and sizes. We find immediate decreases in tissue glucose concentration and simultaneous increases in lactate during neural activation. Both glucose and lactate signals return to their baseline levels instantly as neurons cease firing. No sustained changes or initial dips in glucose or lactate signals are elicited by visual stimulation. However, co‐localized measurements of cerebral blood flow and neural activity demonstrate a clear delay in the cerebral blood flow signal such that it does not correlate temporally with the neural response. These results provide direct real‐time evidence regarding the coupling between co‐localized energy metabolism and neural activity during physiological stimulation. They are also relevant to a current question regarding the role of lactate in energy metabolism in the brain during neural activation. Dynamic changes in energy metabolites can be measured directly with high spatial and temporal resolution by use of enzyme‐based microelectrodes. Here, to examine neuro‐metabolic coupling during brain activation, we use combined microelectrodes to simultaneously measure extracellular glucose, lactate, and neural responses in the primary visual cortex to visual stimulation. We demonstrate rapid decreases in glucose and increases in lactate during neural activation. Changes in glucose and lactate signals are transient and closely coupled with neuronal firing. Abstract : Dynamic changes in energy metabolites can be measured directly with high spatial and temporal resolution by use of enzyme‐based microelectrodes. Here, to examine neuro‐metabolic coupling during brain activation, we use combined microelectrodes to simultaneously measure extracellular glucose, lactate, and neural responses in the primary visual cortex to visual stimulation. We demonstrate rapid decreases in glucose and increases in lactate during neural activation. Changes in glucose and lactate signals are transient and closely coupled with neuronal firing. Read theEditorial Highlight for this article on page639 .